What Africa can do to accelerate and sustain progress against malaria - Fredros Okumu; Margaret Gyapong; Núria Casamitjana; Marcia C. Castro; Maurice A. Itoe; Friday Okonofua; Marcel Tanner (PLOS Global Public Health, 2022)
After a longstanding global presence, malaria is now largely non-existent or suppressed in most parts of the world. Today, cases and deaths are primarily concentrated in sub-Saharan Africa. According to many experts, this persistence on the African continent reflects factors such as resistance to insecticides and drugs as well as insufficient access to essential commodities such as insecticide-treated nets and effective drugs. Crucially, however, this narrative ignores many central weaknesses in the fight against malaria and instead reinforces a narrow, commodity-driven vision of disease control. This paper therefore describes the core challenges hindering malaria programs in Africa and highlights key opportunities to rethink current strategies for sustainable control and elimination. The epidemiology of malaria in Africa presents far greater challenges than elsewhere and requires context-specific initiatives tailored to national and sub-national targets. To sustain progress, African countries must systematically address key weaknesses in its health systems, improve the quality and use of data for surveillance-responses, improve both technical and leadership competencies for malaria control, and gradually reduce overreliance on commodities while expanding multisectoral initiatives such as improved housing and environmental sanitation. They must also leverage increased funding from both domestic and international sources, and support pivotal research and development efforts locally. Effective vaccines and drugs, or other potentially transformative technologies such as genedrive modified mosquitoes, could further accelerate malaria control by complementing current tools. However, our underlying strategies remain insufficient and must be expanded to include more holistic and context-specific approaches critical to achieve and sustain effective malaria control.